Requirements elicitation activity for online internship system / Noorihan Abdul Rahman ... [et al.] - Abdul Rahman, Noorihan; Ahmad Nizam, Nur Marjan Nabilah; Mohd Zin, Nor Asma; Ahmad Zukarnain4, Zuriani (Universiti Teknologi MARA, Kelantan, 2023)
An internship is a part of a working experience in which students are expected to gain working experience by working at a company or organization for a short amount of time as part of the program. The management of student internships has traditionally been handled manually using Microsoft Word and Microsoft Excel, which has resulted in a significant number of duplications. In addition, human error is one of the issues which lecturers and the students typically encounter. Apparently, hardcopy documents are no longer convenient to students, practical coordinators, and the industry representatives. Therefore, the objective of this study is to conduct requirement elicitation activity for obtaining user requirements for an online internship system known as Computer Science Department Internship Information System (CODIIS). The chosen methodology for CODIIS development is the Waterfall model whereby it consists of five phases namely planning, analysis, design, implementation, and maintenance. The requirement elicitation activity results in clear needs on CODIIS which helps to justify the importance of integrating internship-related information.